A Syntactical Analysis on Sentence Structures Spoken by Joe Biden and Donald Trump in the Election Night Speeches - Aries Rahmat Anggoro; Mukhrizal Mukhrizal; Sufiyandi Sufiyandi (Universitas Bengkulu, 2022)
This study attempted to investigate the types of sentence structures spoken by Joe Biden and Donald Trump in the election night speech in the year of 2020. The design of this research was qualitative and quantitative research. The total of 101 sentences of both Joe Biden and Donald Trump were analyzed by using syntactical structure analysis. The instruments of this research were documentation and checklist tables. The data were analyzed by using Miles, Huberman, and Saldana’s theory, and Carnie’s theory was used for the rules in portraying the tree diagram. The results of the study showed that all types of sentence structures appeared in both speeches. In Joe Biden’s speech, there were 40% simple sentence structures, 26.7% complex sentence structures, 16.7% compound sentence structures, and 16.7% compound complex sentence structures. In Donald Trump’s speech, there were 59,2% simple sentence structures, 19.7% complex sentence structures, 15.4% compound sentence structures, and 5.6% compound complex sentence structures. In other words, the simple sentence structures appeared the most dominant in both Donald Trump and Joe Biden speeches. It is recommended that other researchers should study the sentence structures of other American presidents (e.g. Bill Clinton, George W. Bush, and Barrack Obama) in order to expand the descriptions of sentence structures of the US presidents in general.